Extraction of montmorillonite mineral iron-oxides with organic acids - Samsuri, Ariffin; Irawan, Sonny (2003)
Extraction of montmorillonite mineral with high content of iron oxide by means three organic acids (citric, gluconic and oxalic) was studied. The first two release small quantities of iron oxides from the montmorillonite, which means they will not be adequate for large-scale processes. Oxalic acid is capable of dissolving all the extracted iron in montmorillonite, thus making the montmorillonite suitable for its basic industrial application especially in oil and gas industry.